Sexual offenses on campus: Challenges in the disciplinary system - Isaac, Chyanne (Department of Public Law, 2022)
Gender Based Violence (GBV) is not just an institutional problem but a global one. Higher education institutions have come under fire for inadequate policies and processes to address sexual violations on campus. Despite progressive policy revisions and advocacy at South African universities over the years, there is no indication of either a reduction in the number of cases or an increase in confidence in institutional responses to sexual offences. This dissertation reviews the sexual offences policies and procedures at six South African universities and highlights the challenges in the university student disciplinary process. Drawing the distinction between a criminal trial process and administrative hearing process, I make recommendations for procedural changes to the university disciplinary process that protects the complainant in a sexual offences case from unnecessary trauma during hearings.